Query Portals: Dynamically Generating Portals for Web - Agrawal, Sanjay; Chakrabarti, Kaushik; Chaudhuri, Surajit; Ganti, Venky; König, Arnd Christian; Xin, Dong (18th International World Wide Web Conference (WWW 2009), 2009)
Many informational web search queries seek information about named entities residing in structured databases. The information about entities that a user is seeking could be available from the structured database, or from other web pages. For example, consider an informational query such as [lowlight digital cameras]. A large structured database consisting of products may contain several products that are relevant for the user's query. Surfacing a set of the most relevant products to the user and then enabling her to obtain more information about one or more of them would be very useful. Ideally, we would like a portal- like functionality which provides an overview of all relevant products, and further allows drill down on them. The need for structured data search is illustrated by the proliferation of vertical search engines for products, celebrities [2], etc. Current web search engines already federate queries to one or more structured databases containing information about named entities products, people, movies and locations. Each structured database is searched individually and the relevant structured data items are returned to the web search engine. The search engine gathers the structured search results and displays them along side the web search results. However, this approach does not enable a portal-like functionality due to two key limitations.